The Effect of Marketing Mix, Consumer’s Characteristics and Psychological Conditions Toward Purchase Intention of Gucci Among the Millennials in Czechia - Molodzinovska, Vladyslava; Zlatić, Marija; Escobar Rios, Andrea; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
The purpose of this diploma thesis is to investigate the factors that influence the purchase intention of Gucci among the millennials in Czechia. This thesis covers both marketing mix elements and consumer behavior factors to approach the research topic. The literary review casts light on such concepts as purchase intention, marketing mix and consumer behavior, and focuses on findings from the previous studies. The conceptual model is constructed based on theory and other researchers’ findings, and hypotheses are formulated for further statistical testing. To introduce Gucci, which is the brand of interest in this research, the chapter about Gucci background and marketing activities is integrated into this diploma thesis, as well. A quantitative method approach using regression analysis is employed in this thesis. To facilitate the analysis, the statistical software Gretl is used. Results indicate that marketing mix elements, consumer’s characteristics and psychological conditions simultaneously have significant impact on purchase intention of Gucci among the millennials in Czechia. Partially, only place, promotion, social influences, cultural influences and personal influences have significant impact toward purchase intention of Gucci among the millennials in Czechia. The findings of this thesis are important to Gucci’s brand managers and academics as they lay the foundations for the future creation of new strategies and improvements.
Vedoucí práce: Marija Zlatić
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses